Barriers to creativity among students of selected universities in Malaysia - Mohammad Hassan Hilal , Huda; Wan Husin, Wan Nurul Izza; Muhammad Zayed, Tareq (Centre for Promoting Ideas, USA, 2013)

(untitled)
This study aims to identify the most crucial barrier to creativity as experienced by the Malaysian undergraduate students. Second, it assesses the relationship between the Malaysian public universities and the level of severity of creativity barriers. Third, it assesses the difference among students from different faculty of study in relation to the severity of creativity barriers. The Martin's (1990) self-report ‘inventory of barriers to creative thought and innovative action’ was administered to 459 respondents from several universities. The findings revealed that barriers related to task achievement are the most critical barrier to creativity. Meanwhile, the results also showed that there is no significant different among students from different universities in relation to the level of severity of creativity barriers. Similarly, it revealed that there is no significant different among students from different faculties in relation to the severity of creativity barriers. The discussion addresses future research direction.